Optic nerve head changes in esotropia - Al-Haddad, Christiane; Slim, Andre; Wehbi, Zahi; El Hadi, Dalia; Rachid, Elza; Mansour, Ahmad M. (Journal of AAPOS, 2025)
To evaluate the difference in optic disk morphology in eyes with esotropia compared with normal controls. In this prospective, comparative study, the optic nerve heads and axial length of participants with esotropia were compared with those of age- and sex-matched controls. Subjects were examined at the Pediatric Ophthalmology Service of the American University of Beirut between January 2020 and January 2024. Outcome measures were acquired using OCT and IOL Master. A total of 174 participants were enrolled: 83 esotropic subjects (mean age, 11.22 ± 4.58 years; female, 57%) and 91 controls (age, 11.47 ± 4.72 years; female, 59%). Mean spherical equivalent was higher in the esotropia group (right eye, 3.62 ± 2.49 D; left eye, 3.63 ± 2.59 D) than in controls (right eye, 0.59 ± 1.67 D; left eye, 0.66 ± 1.64 D) (P < 0.001 for both eyes). Optic disk area and rim area were larger in patients; however, the difference was not statistically significant after adjusting for hyperopia and axial length (AL). Esotropic patients had significantly smaller average cup:disk ratios than controls (0.29 vs 0.36 [P = 0.01] for right eyes and 0.28 vs 0.35 [P = 0.03] for left eyes) and smaller cup volumes (0.06 vs 0.09 mm3 [P = 0.01] for right eyes and 0.05 vs 0.10 mm3 [P = 0.002] for left eyes) After adjusting for hyperopia and AL, cup:disk ratio and cup volume remained significantly smaller among patients. Retinal nerve fiber layer tended to be thicker among patients, though not significantly. Optic nerve head cup volume and cup:disk ratio were significantly smaller in patients with esotropia, independent of refraction and axial length.